DEVELOPMENT OF FORMATIVE TEST INSTRUMENTS BASED ON PLICKERS APPLICATION ON HUMAN EXCRETORY SYSTEM MATERIALS - Dewi, Cut Ratna; Elvita, Wittria (Jurnal Biologi Sains dan Kependidikan, 2024)
Assessment plays a crucial role in the learning process, involving the systematic analysis of data collected from students' learning outcomes throughout the educational journey. One type of assessment implemented is formative assessment. This study aims to explore the steps involved in developing a formative test instrument using the Plickers application for teaching the human excretory system in SMP/MTsN. The research follows a Research and Development approach. The findings reveal the stages in developing the formative test instrument with Plickers, which include creating an account, setting up a class, formulating questions, downloading Plickers cards, and installing the Plickers app from the Play Store. The study concludes that the Plickers application is user-friendly for teachers and provides an enjoyable learning experience for students.